Approximate orthogonality in complex normed spaces: a directional approach. Issue 5 (24th March 2023) - Roy, Saikat; Sain, Debmalya
Abstract : We introduce and study the notion of approximate directional orthogonality in a complex normed space. We further explore the relevant scenario in the topological setting, which allows us to characterize approximate Birkhoff–James orthogonality of operators on a finite-dimensional complex Banach space. Our investigation extends some existing results in the literature to a broader scope.